DESIGN PATTERN COMPONENTIZATION. - Meyers, Scott (Computer (00189162), 2006)
A letter to the editor is presented in response to the article "Componentization: The Visitor Example," by Bertrand Meyer and Karine Arnout in the July 2006 issue.